Revitalisasi Ukhuwah Islamiyah Melalui Program Berbagi Sosial Keagamaan di Desa Allaere Kecamatan Tanralili Kabupaten Maros: Revitalization of Islamic Brotherhood Through a Socio-Religious Sharing Program in Allaere Village, Tanralili District, Maros Regency - Rosmita; Akhmad Hanafi Dain Yunta (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
Socio-religious activities play a crucial role in strengthening solidarity and Islamic brotherhood within communities. This article describes efforts to revitalize Islamic brotherhood through a series of socio-religious sharing programs in Allaere Village, Tanralili District, Maros Regency. The programs included distributing dates before iftar, organizing communal fast-breaking, distributing Iqra and Dirosah books to enhance religious literacy, conducting social services, and delivering food packages to underprivileged residents. This study employed a descriptive qualitative method using field observations and documentation. The findings indicate that these sharing activities enhanced social interaction, reinforced emotional ties among residents, and fostered a spirit of cooperation and care for others. Additionally, the programs increased community participation in religious and social activities, reflecting strengthened Islamic brotherhood values. Overall, the socio-religious sharing movement proved to be an effective approach to promoting harmony, collective awareness, and social resilience in a rural Islamic community.